A case report and literature review of livedoid vasculopathy in children - Qu, Jing; Hao, Zhihong; Junli, Wang; Yu, Shengyou (Frontiers in Pediatrics, 2025)
BackgroundLivedoid vasculopathy (LV) is a rare, non-inflammatory, intradermal vascular obstructive skin disorder characterized by purpuric papules and plaques with capillary dilation. These lesions typically progress to crusted ulcers and ultimately result in fixed, white, atrophic stellate scars. The condition is marked by painful ulcers that heal slowly and have a tendency to recur.Case presentationWe report a case of a pediatric patient presenting with recurrent rashes and pain in both lower extremities. Physical examination revealed purpuric plaques with ulceration, scarring, and white atrophic healing features. Histopathological examination demonstrated intradermal thrombosis, vessel wall necrosis, and surrounding inflammatory cell infiltration with erythrocyte extravasation. Periodic acid-Schiff (PAS) staining was positive. The clinical and pathological findings were consistent with a diagnosis of LV. The patient was treated with oral rivaroxaban.ConclusionThis case highlights the critical importance of early recognition and intervention in the management of LV. Clinicians should consider LV in the differential diagnosis when encountering patients with painful purpuric rashes. Improvement in pain following treatment with anticoagulants, such as rivaroxaban, may indirectly support the diagnosis. A skin biopsy is essential for definitive diagnosis.